2017
DOI: 10.1007/s00270-017-1765-3
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Adverse Events Related to Prostatic Artery Embolization for Treatment of Bladder Outlet Obstruction Due to BPH

Abstract: Regarding safety, it is pivotal to understand the pathophysiology of adverse events following PAE and their standardized reporting. The aim of this article is to discuss adverse events, their management and to review the current literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 66 publications
0
56
0
3
Order By: Relevance
“…A postembolization syndrome, which can include pain, dysuria, frequency, and other irritative symptoms, is anticipated following PAE. These effects typically last less than 1 week and require only symptomatic management (57). Minor complications requiring therapy include acute urinary retention requiring temporary catheterization in 2.5%-4.6% of patients and urinary tract infection requiring oral antibiotic therapy in 2.6%-7.6% of patients (51).…”
Section: Safety Of Paementioning
confidence: 99%
See 1 more Smart Citation
“…A postembolization syndrome, which can include pain, dysuria, frequency, and other irritative symptoms, is anticipated following PAE. These effects typically last less than 1 week and require only symptomatic management (57). Minor complications requiring therapy include acute urinary retention requiring temporary catheterization in 2.5%-4.6% of patients and urinary tract infection requiring oral antibiotic therapy in 2.6%-7.6% of patients (51).…”
Section: Safety Of Paementioning
confidence: 99%
“…Major complications following PAE are rare. In review of more than 2,000 patients in the 17 unique cohort studies and 6 comparative trials, a total of 6 major complications were encountered (Table 3) (30,50,57,58). Two cases required surgical intervention; both were cases of bladder ischemia requiring partial resection (30,50).…”
Section: Safety Of Paementioning
confidence: 99%
“…Die Effektivität der Embolisation scheint sowohl mit kleinen als auch großen Partikeln gleichwertig zu sein [34]. Allerdings ergeben sich Hinweise, dass bei Verwendung von kleineren Partikeln (100-300 µm) etwas häufiger unerwünschte Ereignisse auftreten [35]. Dies ist in erster Linie durch eine tiefere Penetration der kleineren Partikel zu erklären, die wohl eine stärkere ischämische und dementsprechend auch eine größere nekrotische Wirkung nach sich ziehen.…”
Section: Embolisationstechnikunclassified
“…In the case of PAE, this requires intraprocedural cone beam CT (CBCT) to confirm catheter placement and exclude nontarget embolization. 18,22 In fact, CBCT provides essential information not seen during digital subtraction angiography (DSA) alone in 60.8% of cases. 18 Additionally, a recent study demonstrated that CBCT identifies the PA with improved discrimination and less radiation dose than conventional preprocedural CTA.…”
Section: Cone Beam Ctmentioning
confidence: 99%
“…This typically consists of urinary frequency and dysuria lasting up to 5 days. 22 Patients are subsequently seen 1, 3, 6, and 12 months following PAE for clinical assessment. Imaging assessment with postprocedural MRI is obtained at 6 months if comparative preprocedural imaging is available.…”
Section: Post-procedural Managementmentioning
confidence: 99%